False positive Wassermann reaction associated with evidence of enterovirus infection - Quaife, R. A. (1971)
A large proportion of high titre Coxsackie B5 complement-fixation tests was detected among sera giving false positive Wassermann reactions during 1969. Echo virus type 9 proved to be the prevailing enterovirus and is one of those which induces the formation of antibody to Coxsackie B5. One case of Echo virus type 9 meningitis is presented which produced a false positive Wassermann reaction and a high titre Coxsackie B5 complement-fixation test. The relationship between Echo virus type 9 infection, Coxsackie complement-fixation test results, and false positive Wassermann reactions is considered significant.